Mycobacterium fortuitum and Polymicrobial Peritoneal Dialysis-Related Peritonitis: A Case Report and Review of the Literature - Anwar Hamade; Agnieszka Pozdzik; O. Denis; Monika Tooulou; Caroline Keyzer; F. Jacobs; Jose Khabbout; Joëlle L. Nortier (Case Reports in Nephrology)
Mycobacterium fortuitum is a ubiquitous, rapidly growing nontuberculous mycobacterium (NTM). It is the most commonly reported NTM in peritoneal dialysis (PD) associated peritonitis. We report a case of a 52-year-old man on PD, who developed refractory polymicrobial peritonitis necessitating PD catheter removal and shift to hemodialysis. Thereafter, M. fortuitum was identified in the PD catheter culture and in successive cultures of initial peritoneal effluent and patient was treated with amikacin and ciprofloxacin for six months with a good and sustained clinical response. Months after completion of the course of antibiotics, the patient successfully returned to PD. To our knowledge, this is the first reported case of M. fortuitum peritonitis in the field of polymicrobial PD peritonitis. It demonstrates the diagnostic yield of pursuing further investigations in cases of refractory PD peritonitis. In a systematic review of the literature, only 20 reports of M. fortuitum PD peritonitis were identified. Similar to our case, a delay in microbiological diagnosis was frequently noted and the Tenckhoff catheter was commonly removed. However, the type and duration of antibiotic therapy varied widely making the optimal treatment unclear.